The jihadist terrorism - Cutrale, Elisabetta (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2019)
Following a general introduction to understand the issues of the Islamic world and the meaning of some key words, the writing carries out an investigation into the phenomenon of the jihadist terrorism. Beginning with a brief on the debate on the definition of international terrorism, the article looks into the islamic state system, its evolucion during the last period and the increasing of violent radicalization. Considering severals studies and statistics, it tries to clarify the causes of the terrorist deviation, reaching the conclusion that it is a complex phenomenon that embraces historical, social and psychological matters.
Keywords: terrorism; islamic fundamentalism; violent radicalization; terrorist; Islam